Workplace stressors, psychological well‐being, resilience, and caring behaviours of mental health nurses: A descriptive correlational study - Foster, Kim; Roche, Michael; Giandinoto, Jo‐Ann; Furness, Trentham (International journal of mental health nursing, 2020)
There is widespread recognition that workplace stress can have profound negative impacts on nurses’ well‐being and practice. Resilience is a process of positive adaptation to stress and adversity. This study aimed to describe mental health nurses’ most challenging workplace stressors, and their psychological well‐being, workplace resilience, and level of caring behaviours, explore the relationships between these factors, and describe differences in workplace resilience for sociodemographic characteristics. In a descriptive correlational study using convenience sampling, data were collected from N = 498 nurses working in mental health roles or settings in Victoria Australia via an online cross‐sectional survey. Key findings included weak to strong (r = 0.301 to r = 0.750) positive relationships between workplace resilience with psychological well‐being across all stressor categories (consumer/carer; colleague; organizational role; and organizational service). Psychological well‐being was moderately high, but lower for nurses indicating consumer/carer‐related stressors as their most stressful challenge. There were weak to moderate (r = 0.306 to r = 0.549) positive relationships between workplace resilience and psychological well‐being, and no relationship between resilience and caring behaviours. Workplace resilience was lower (P < 0.05) for less experienced nurses compared with those with >5 years’ experience, and lower for younger nurses compared with those aged ≥40 years. To improve their resilience and prevent psychological distress, there is prime opportunity to support nursing students with well‐being and resilience‐building strategies during their undergraduate education, and to support new graduates with similar programmes when they enter the workforce.